Associations between the performance of vertical jump and accelerative sprint in elite sprinters - He, Junliang; Li, Ming; Zhang, Qiuping; Zhang, Zhiye (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe purpose of this study is to investigate the relationship between components of the Sprint Profile during acceleration and kinematic and kinetic measures of the Counter Movement Jump (CMJ) and Squat Jump (SJ), to determine whether jump performance can monitor acceleration performance in sprinting.MethodsEight elite sprinters offered to participate in the study (mean ± SD: age 21.43 ± 3.6 years; height 171.58 ± 7.76 cm; weight 54.71 ± 6.05 kg). The training age of athletes was 8.86 ± 4.30 years, which included SJ, CMJ, and accelerative sprint tests.ResultsSignificant negative correlations were found between propulsion time and braking time during sprint acceleration and CMJ metrics, including flight time, jump height, vertical take-off velocity, and push impulse (r = −0.598 to −0.721, p < 0.01). Similar associations were observed for SJ variables, though generally with slightly lower correlation strength. Ground contact time during sprinting was positively correlated with CMJ and SJ metrics (p < 0.05). Additionally, several sprint-phase kinetic variables—such as horizontal and vertical propulsion impulses—showed significant negative correlations with both CMJ and SJ outcomes. These findings suggest that specific jump performance measures, particularly from CMJ, may serve as effective monitor of acceleration sprint performance.ConclusionThis study confirms that key countermovement jump and squat jump metrics, especially jump height and flight time, are significantly associated with sprint acceleration in elite athletes. These findings support the use of jump tests as practical tools to monitor and enhance acceleration performance through targeted lower-limb power training.